The Development of Nano-mist Spray Propolis as Antioxidant - Suryaman, Ine Suharyani; Sulastri, Lela; Rizikiyan, Yayan; Wathoni, Nasrul; Suhandi, Cecep; Noviani, Lusy; Rahmasari, Yuni (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Propolis is a lipid-based compound from honeybees composed of plant wax, resin, and pollen. Due to its poor water solubility, its application is limited to lipid-based formulations with low bioavailability. This study aimed to develop a water-based propolis nano-mist spray with improved dispersion and evaluate its antioxidant activity. The nano-mist formulation was prepared using soy lecithin and Tween 80 in a phosphate buffer base. Evaluations included organoleptic characteristics, pH, particle size, zeta potential, and antioxidant activity by DPPH method. The propolis extract contained flavonoids, alkaloids, and tannins. The resulting spray showed a light brown color, a pH of 6.87 ± 0.03, particle size of 272.13 ± 4.25 nm, and zeta potential of -0.433 ± 0.35 mV. Antioxidant testing revealed moderate activity with an IC₅₀ value of 83.63 ± 11.88 ppm. This study supports the potential of nano-mist spray as a promising delivery system for propolis with antioxidant properties suitable for cosmetic and pharmaceutical applications.